2022
DOI: 10.3389/fpubh.2022.991040
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 2 seroprevalence and associated factors in fertility-treatment-seeking population: A cross-sectional survey in the United Arab Emirates

Abstract: BackgroundHerpes simplex virus type 2 (HSV-2) is a common genitally-transmitted viral infection affecting more than 400 million individuals globally. In the United Arab Emirates (UAE), in specific at-risk population groups, the burden of HSV-2 has not been reported. This study investigated the prevalence of HSV-2 IgG antibodies in patients seeking fertility treatment and characterized patients with seropositivity to HSV-2 IgG antibodies.MethodologyA cross-sectional sample of patients seeking fertility treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…In a study conducted in China by Han et al [52], the prevalence of TOX, CMV and RV was found to be 3.20% (95% CI: 3.18-3.22%), 77.67% (95% CI: 77.62-77.71%) and 76.03% (95% CI: 75.98-76.07%), respectively. Abdo et al [53] in the United Arab Emirates reported a prevalence of 12.4% for HSV-2. A multitude of factors, including nutritional status, vaccination status, socio-cultural habits, geographical and climatic variations, route of transmission, age, and others, in uence the prevalence of TORCH infections.…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted in China by Han et al [52], the prevalence of TOX, CMV and RV was found to be 3.20% (95% CI: 3.18-3.22%), 77.67% (95% CI: 77.62-77.71%) and 76.03% (95% CI: 75.98-76.07%), respectively. Abdo et al [53] in the United Arab Emirates reported a prevalence of 12.4% for HSV-2. A multitude of factors, including nutritional status, vaccination status, socio-cultural habits, geographical and climatic variations, route of transmission, age, and others, in uence the prevalence of TORCH infections.…”
Section: Discussionmentioning
confidence: 98%
“…In natural human infections, HSV-2 primarily spreads through intimate genital tract contact, resulting in persistent infection [14]. The World Health Organization (WHO) reports that 491 million sexually active individuals aged 14-49 harbor HSV-2, with an estimated 12% global prevalence of genital herpes in 2015 [15][16][17]. Approximately 400 million people are at risk of genital herpes with latent persistence, with women having a twofold higher seropositivity than men [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…HSV-2 primarily manifests as genital ulcer disease (GUD) and can cause neonatal infections, inflammation, and, less frequently, ocular infections, encephalitis, and meningitis [8,[30][31][32][33][34][35]. Immunocompromised individuals and neonates face more severe HSV-2 infections due to various genetic, immune, and epigenetic factors [17,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation